중기(中氣)로 인한 좌상하지마비(左上下肢麻痺) 환자 증례보고 - 김헌일; Hun Il Kim; 김근우; Geun Woo Kim; 구병수; Byung Soo Koo (동의신경정신과학회지, 2004)
Objectives: The purpose of this study is about oriental medicine's treatment and approach method of conversion disorder(jungkijeung) Methods: We observed the treatment effectiveness of herb-med, acupunture, physical therapy about conversion disorder(jungkijeung) Result and Conclusions: We try to present the possibility of the approach method about conversion disorder. 1. We should treat conversion disorder(jungkijeung) distinguished Gi deficiency(氣虛) between vigorous gi(氣寶) 2. The acupunture treatment of conversion disorder(jungkijeung) is efficient about all sorts symptoms and pain 3. Dyscinesia's sequela due to conversion disorder(jungkijeung) is possible to be protracted 4. It is important to prevent sick role, and for this, to use physical therapy is efficient about dyscinesia's patient due to conversion disorder(jungkijeung)